2008
DOI: 10.1111/j.1365-2850.2008.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Destructive Whirlwind’: nurses' perceptions of patients diagnosed with borderline personality disorder

Abstract: Research suggests that nurses have negative perceptions and subsequently negative interactions with patients diagnosed as having Borderline Personality Disorder (BPD). However, this research is mainly quantitative in nature and does not allow nurses to speak freely about their experiences of working with this client group. The purpose of this study was to explore nurses' relationships with BPD patients from their own perspective. Semi-structured interviews were used to elicit the participants' experiences of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 14 publications
7
91
0
Order By: Relevance
“…schizophrenia and depression (Markham & Trower, 2003;Forsyth 2007;Westwood & Baker, 2010), and may also be less optimistic about the potential of people with BPD to recover (Markham & Trower 2003), viewing them as more difficult to care for compared to other service users (James & Cowman, 2007;Howes, Weaver, & Tyrer, 2008). Woollaston & Hixenbaugh, 2008 found that some nursing staff felt they lacked the necessary skills to work with people with BPD, but wanted to improve their practice with this service user group. A need to develop skills in working with BPD was also a theme evident within the literature reviewed by Westwood & Baker (2010).…”
Section: Introductionmentioning
confidence: 99%
“…schizophrenia and depression (Markham & Trower, 2003;Forsyth 2007;Westwood & Baker, 2010), and may also be less optimistic about the potential of people with BPD to recover (Markham & Trower 2003), viewing them as more difficult to care for compared to other service users (James & Cowman, 2007;Howes, Weaver, & Tyrer, 2008). Woollaston & Hixenbaugh, 2008 found that some nursing staff felt they lacked the necessary skills to work with people with BPD, but wanted to improve their practice with this service user group. A need to develop skills in working with BPD was also a theme evident within the literature reviewed by Westwood & Baker (2010).…”
Section: Introductionmentioning
confidence: 99%
“…This stems from the belief that their behaviour is calculated and dishonest rather than being part of their illness (Westwood and Baker 2010). A view of this nature could effect the calibre of care a nurse delivers and will lead to the patient feeling rejected and devalued; a feat which will cause further deterioration of their illness (Woollaston and Hixenbaugh 2008). These findings can be related to the experiences of student nurses in order to appreciate the thought process of the nurses involved.…”
Section: Criterion -Borderline Personality Disordermentioning
confidence: 99%
“…Studies have found words such as time-wasters, manipulative, difficult or attention-seeking are used to describe these patients. Some staff believe that patients with BPD are in control of their behaviour and are therefore manipulative and dangerous (Woollaston and Hixenbaugh 2008). Health care professionals working in mental health settings are more likely to have negative attitudes and perceptions of people with PD than any other diagnosis, which may influence the standard of care this patient group receives (Fraser and Gallop 1993;Markham 2003).…”
Section: Criterion -Borderline Personality Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicating that the stigma of mental illness has an effect on mental health outcomes has led to increased study of stigmatizing attitudes among mental health providers, both of individuals providing service Woollaston, & Hixenbaugh, 2008) and of mental health care program settings (Flanagan, Miller, & Davidson, 2009;Holley, Tavassoli, & Stromwall, 2016). Researchers have already called upon medical professionals, such as physicians and nurses, to become more aware of the stigmatizing attitudes that have negatively impacted the medical care of their patients with mental illnesses (Clarke et al, 2007;Freidrich et al, 2013;Sadow et al, 2002).…”
Section: Stigma Of Mental Illness Among Mental Health Care Providersmentioning
confidence: 99%